Evaluation of the capacity for environmental management of the municipalities of the Alagoas sertão / Avaliação da capacidade para a gestão ambiental dos municípios do sertão alagoano - Eles Calheiros Marques Junior; Ana Luzia de Barros Andrade Marques (Universidade Estadual de Alagoas, 2018)
Concern about the preservation of the environment has gained strength in the world and Brazilian scenario especially since the 1960s, and has been included in the agenda of the Academy, the business world, organized civil society and the Public Power. In Brazil, with the advent of the PNMA (Law No. 6,938, dated August 31, 1981) and the Federal Constitution of 1988, the protection and defense of the environment became the competence and attribution of the Federal, State and Municipal levels. Regarding the latter, it is necessary to analyze whether the Brazilian municipalities have the capacity to efficiently, effectively and effectively conduct local environmental management. Thus, the general objective of this work is to evaluate if the municipalities of the mesoregion of the Alagoan sertão have the capacity for environmental management. As a specific objective, it is intended to classify the municipalities of the sertanejos according to the degree of installed capacity for the environmental management, and to elaborate the spatial representation of this classification. To meet the stated objectives, an exploratory-descriptive research was carried out, with a quantitative approach, using bibliographical review and documentary analysis. As a result, it was found that most of the municipalities in the hinterland of Alagoas do not have environmental management tools that enable them to adequately manage local natural resources in response to the demands of citizens and environmental legislation in force in Brazil.